2020
DOI: 10.26803/ijlter.19.7.14
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Higher Order Thinking Skills (HOTS) Module Based on the Cognitive Apprenticeship Model (CAM) on Student’s Performance

Abstract: This study intended to examine the difference in students' performances in terms of measurement and geometry between urban and rural schools. This research used a quasi-experimental design. This study involved a total of 63 students from urban school and 51 students from the rural school. This study conducted a pre-test, post-test, and post-delayed test to measure the students' performance. The treatment group utilized the Higher Order Thinking Skills (HOTS) based Module framed Cognitive Apprenticeship Model (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…The module also describes the complete material and study case for online learning to increase the affective domain (Bower et al, 2015;Li et al, 2016). In addition, the module also has detailed project examples to improve the students' psychomotor (Huang, 2020;Ibrahim et al, 2020). The completeness of the material also needs descriptions and pictures that expand students' imagination when they examine the module (Choi et al, 2019;Mora et al, 2020).…”
Section: Need Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The module also describes the complete material and study case for online learning to increase the affective domain (Bower et al, 2015;Li et al, 2016). In addition, the module also has detailed project examples to improve the students' psychomotor (Huang, 2020;Ibrahim et al, 2020). The completeness of the material also needs descriptions and pictures that expand students' imagination when they examine the module (Choi et al, 2019;Mora et al, 2020).…”
Section: Need Analysismentioning
confidence: 99%
“…They must refer to the two standard operating manuals to train them to work in the appropriate standard procedures in their work, as Huang et al (2020) described. For high-order thinking, as suggested by Leaman and Flanagan (2013) and Ibrahim et al (2020), the significance of following the analysis procedure during the work process is to maintain the steering, brakes, and suspensions to comfort the driver and passengers of the vehicle. Therefore, the components should be maintained under predetermined standards.…”
Section: Student Psycomotor Analysismentioning
confidence: 99%
“…The authors of [33] developed a model of instruction based on the coaching method of cognitive apprenticeship theory, which was applied to K-8 writing instruction. The authors of [34] presented the result that students' performance can be improved by utilizing higher-order thinking skills based on cognitive apprenticeship theory. The authors of [35] presented the integration of a cognitive apprenticeship model with a coaching method to construct an instructional model on devising higher-order cognitive skills, which can be applied in management education.…”
Section: Catmentioning
confidence: 99%
“…The combination is an advanced instructional model that goes beyond the basic transfer of content but fosters critical thinking and problem-solving skills typically found in expert practice (Powell & Stansell, 2014). Studies have shown that the combination results in an increase in students' understanding of the concept of the subject matter (Ibrahim, Ayub, & Yunus, 2020). CA is based on the theory of situated learning where knowledge is acquired and contextually tied to the settings and situations in which it is learnt and PBL has been shown to increase expertise level by providing an authentic experience through projects.…”
Section: Pbl and Camentioning
confidence: 99%